Морфология личинки Wohlfahrtia balassogloi Portsch., 1882 (Diptera, Sarcophagidae) - Валентюк, Е.И. (Вестник зоологии, 1972)
A description is given in all three ages in Wohlfahrtia balassogloi P o r t s c h maggot. Morphological characters of each age are distinguished